2009
DOI: 10.1088/0256-307x/26/12/124214
|View full text |Cite
|
Sign up to set email alerts
|

Mid-IR Dual-Wavelength Difference Frequency Generation Using Fiber Lasers as Pump and Signal Light Sources

Abstract: A continuous-wave mid-IR difference frequency laser source, which respectively uses an ytterbium-doped fiber laser as the pump source and a multiwavelength erbium-doped fiber laser cascaded with an erbium-doped fiber amplifier as the signal source, is demonstrated. Our experimental results show that two stable mid-IR radiation lines with a spacing of about 5.4 nm may be simultaneously emitted by a suitable setting the pump and signal polarization orientations. The number of the mid-IR radiation lines is limite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…In addition, the laying concentration of proppant has a certain influence on the embedding depth [10] . In 2018, Su analyzed the influence of proppant embedding through experiments and concluded that with the increase of closing pressure, the conductivity of proppant decreased obviously, and the conductivity of proppant with small particle size decreased slightly [11] . In 2020, Liu pointed out that the conductivity of ceramsite proppant is stronger than quartz sand and coated sand among the influencing factors of hydraulic fracturing support fracture in shale reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the laying concentration of proppant has a certain influence on the embedding depth [10] . In 2018, Su analyzed the influence of proppant embedding through experiments and concluded that with the increase of closing pressure, the conductivity of proppant decreased obviously, and the conductivity of proppant with small particle size decreased slightly [11] . In 2020, Liu pointed out that the conductivity of ceramsite proppant is stronger than quartz sand and coated sand among the influencing factors of hydraulic fracturing support fracture in shale reservoirs.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, an irregularly engineered QPM grating can only perform the fixed function, i.e., the designed function. Recently, by using the dispersion property of the periodically poled niobate (PPLN), Jiang et al [12] presented a novel dual-wavelength mid-IR DFG laser source based on a near-IR multiwavelength erbium-doped fiber laser (EDFL) and an ytterbium-doped fiber laser (YDFL). Two stable mid-IR radiation lines with a spacing of about 5.4 nm were simultaneously achieved, which may also be synchronously tuned between 3295 nm and 3356.3 nm.…”
Section: Introductionmentioning
confidence: 99%
“…We present here an alternative frequency generation (DFG) in a (NIR) fiber lasers that are comm others groups [4][5][6], but the lates scanning picoseconds fiber laser Laser (SPL) from Genia Photoni output pulses are synchronized at should be intrinsically robust to mechanical vi ble over a broad spectral range, and effici could meet all these goals is the MIR fiber laser. sers do not exist yet, and they still require nd highly efficient pump sources [2].…”
mentioning
confidence: 99%